Synthesis of mono-fluoromethyl 6, 5-heteroaromatic bicycles using 1, 3-difluoroacetone as a cyclising reagent. (26th October 2022) - Cosgrove, Brett; Clissold, Cole; Malagu, Karine; Chambers, Mark; Dominguez, Celia; Liu, Longbin
Graphical abstract: Het= pyridine, pyrimidine, pyrazine and pyridazine Abstract: The development of facile, wide scope synthetic methodologies providing access to fluorinated motifs is important in medicinal chemistry; for our purposes, we are interested in developing fluorine-tagged compounds to investigate their utility in Huntington's disease. Here, we describe a novel, operationally simple and mild procedure for the synthesis of mono-fluoromethyl 6, 5- heteroaromatic bicycles using 1, 3-difluoroacetone (DFA). The scope of the reaction was investigated, and 25 examples synthesized with yields up to 96%.